The effect of vascular access type on intra-access flow volume during hemodialysis. Issue 6 (November 2019) - Park, Hoon Suk; Kim, Woo Jeong; Choi, Joonsung; Kim, Hyung Wook; Baik, Jun Hyun; Kim, Young Ok; Park, Cheol Whee; Yang, Chul Woo; Jin, Dong Chan
Introduction: Previous studies have revealed that vascular access resistance is constant during hemodialysis, but differs according to vascular access type. It is possible that intra-access flow volume (Qac) variation during hemodialysis may also differ according to vascular access type. We conducted this study to investigate whether there are differences in Qac according to vascular access type during hemodialysis. Methods: A total of 58 lower-arm arteriovenous fistula, 14 lower-arm arteriovenous graft, 27 upper-arm arteriovenous fistula, and 45 upper-arm arteriovenous graft cases were studied. Three consecutive Qac values (at 30, 120, and 240 min after the start of hemodialysis) were measured in each patient by the ultrasound dilution technique. Variations in Qac over time were analyzed using repeated measures analysis of variance and multivariate regression analyses, to assess the impact of different factors on Qac variation. Results: The repeated measures analysis of variance revealed that a significant interaction exists between time and vascular access type (p < 0.001). This suggests that vascular access type affects Qac change (%) variation over time during hemodialysis. In a multivariate analysis, mean arterial pressure change during hemodialysis (p = 0.009), access type (p < 0.001), and access location (p < 0.001) were independent variables causing Qac change variation. Conclusion: This study showed that there is a significant difference in Qac variation according to vascular access type during hemodialysis and that arteriovenous graft (vs arteriovenous fistula) and the lower-arm location (vs upper arm) were associated with a decrease in Qac during hemodialysis. This suggests that consideration of vascular access type is required to minimize Qac variation during hemodialysis.